الثقافة التنظيمية وأثرها على الإنتاجية: (دراسة حالة مصنع فيرست للمواد الغذائية) - د. شريف محجوب محمد يوسف; د. مجدي ابراهيم زكريا محمد (White Nile Journal for Studies and Research, 2026)
This study dealt with the organizational culture and its impact on productivity in the First Food stuff Factory. The study aimed to identify the impact of the elements and dimensions of the organizational culture represented in (values, beliefs, norms, expectations) on productivity in its two dimensions (efficiency, effectiveness). The study relied on the historical and descriptive analytical method, using the Statistical Analysis Program for Social Sciences (SPSS), and among the methods that were used in the study (Alpha Cronbach, descriptive analysis methods, regression), and the study population was represented by the employees of the First Foodstuff Factory, who numbered (344). The simple random sampling method was used, and the study relied on the questionnaire as a main tool in data collection, and it was analyzed according to the five-point Likert scale. (182) questionnaires were distributed, and (168) valid questionnaires were retrieved for analysis any percentage (92.3%). The study reached several results, the most important of which are: the existence of a positive and significant relationship between organizational culture in its dimensions of (values, beliefs, norms, expectations) and productivity in its dimensions (efficiency, effectiveness), and there is no significant relationship between organizational norms and productive effectiveness, and that there is an increase in Workloads placed on factory workers, and that the prevailing organizational culture in the factory is a mixture between strong organizational culture and adaptive organizational culture, and that prevailing organizational values in the factory are discipline, respect for time, quality, adherence to health requirements, respect and cooperation among colleagues, teamwork, adherence to laws and regulations. In the light of the results, the study recommended several recommendations, the most important of which are: maintaining the positive and moral level of the prevailing organizational culture, reducing the workload assigned to workers in proportion to the job, expanding the participation of workers in decision-making, and informing all factory workers of the development plans for work.